Profil gaya belajar siswa SMA kelas X pada materi sistem persamaan linear tiga variabel (SPLTV) - Munaroh, Siti Alip; Sania Effendi, Kiki Nia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research aims to describe the learning style profile of class Descriptive research with a qualitative approach is the method used in this research. This research was carried out in class X at a public high school in Karawang Regency. The subjects used were 36 class X students for the 2023/2024 academic year. Data processing was carried out by giving questionnaires to students and then analyzing them so that 3 students were selected as research subjects until the end, one student with a visual learning style, one student with an auditory learning style and one student with a kinesthetic learning style. Three selected students were given questions regarding Systems of Linear Equations with Three Variables (SPLTV). The selection of research subjects was taken from students in the medium category. Based on the research results, it was found that the learning style that is most widely used is the auditory learning style and the average result of working on SPLTV questions is 49.82, which shows that this value is below the KKM. Thus, students' ability to solve SPLTV questions is in the low category.